Corporatization of the Jesus M. Colmenares District Hospital in Balasan, Iloilo a feasibility study - Bullo, Edron Jr. T.
The researchers conducted this study to determine if corporatization of the Jesus M. Colmenares District Hospital in Balasa, Iloilo is feasible, and if it is the best alternative to the present problems of the hospital. The researchers also wanted to konw the possible effects of corporatization to the operation of the hospital and to its employees as well. Another purpose of the study is to determine the acceptability of corporatization to the hospital employees. Important hospital records were gathered such as financial statements and list of facilities. The researchers also sought technical assistance from the Department of Health, Provincial Health Office, and from the four catchment municipalities of Jesus M. colmenares District Hospital. The researchers decided to consider the age of the employees, their civil status and their department assigned. The study would be of help to the development of the Jesus M. Colmenares District Hospital in improving their services and facilities. This study will also help in uplifting the services of the health sector specifically in rural areas like Balasan, iloilo. The respondents of the study were the hospital employees. The research instrument used was the questionnaire. The researchers made use of the survey method. After the presentation of findings and analysis, the researchers came up with the conclusion that hospital corporatization is feasible and that it is the best alternative in uplifting the services and facilities of Jesus M. Colmenares District Hospital. The researchers also concluded that the said variables : age, civil status, and department assigned, affected the hospital employees' perception and acceptability of corporatization. The researchers' recommendation is to implement the hospital corporatization to Jesus M. Colmenares district Hospital to improve the services and facilities of the hospital and to uplift the health condition of the four catchment municipalities.